185k views
0 votes
Which applies the power of a power rule to simplify the expression 8^12 3

Which applies the power of a power rule to simplify the expression 8^12 3-example-1

2 Answers

0 votes
B.

When you raise a number to a power, you multiply its current power with the one you're raising it to.
User Gullbyrd
by
5.8k points
6 votes

Answer:

Option (b) is correct.


(8^(12))^3=8^(12* 3)=8^(36)

Explanation:

Given : the expression
(8^(12))^3

We have to simplify the given expression and choose the correct from the given options.

Consider the expression
(8^(12))^3

Using property of exponents,


\left(a^b\right)^c=a^(b* c)

We have,


(8^(12))^3=8^(12* 3)=8^(36)

Thus, Option (b) is correct.


(8^(12))^3=8^(12* 3)=8^(36)

User Geeky
by
5.8k points